Biodegradation: Magneto‐Thermal Metrics Can Mirror the Long‐Term Intracellular Fate of Magneto‐Plasmonic Nanohybrids and Reveal the Remarkable Shielding Effect of Gold (Adv. Funct. Mater. 9/2017). (March 2017) - Mazuel, François; Espinosa, Ana; Radtke, Guillaume; Bugnet, Matthieu; Neveu, Sophie; Lalatonne, Yoann; Botton, Gianluigi A.; Abou‐Hassan, Ali; Wilhelm, Claire
Abstract : Biodegradation of magneto‐plasmonic nanohybrids (magnetic, gold‐decorated nanoflowers) are investigated within a multi‐faceted cellular environment by Ali Abou‐Hassan, Claire Wilhelm, and co‐workers in article number 1605997. Two extreme transformations are evidenced: the gold seeds are either released from magnetic cores which almost entirely dissolve and load ferritin with free iron (left), or the gold shell almost completely protects the magnetic core from dissolution (right).